Concomitant presentation of myocarditis and non-bacterial thrombotic endocarditis in a patient with granulomatosis with polyangiitis (Rheumatology Reports, 2014)
Granulomatosis with polyangiitis (GPA) is a necrotizing vasculitis. The etiology of the disease is not completely known. In this report, we describe a 47-year-old male who presented with ongoing dyspnea. He is a known case of GPA for 3 years based on skin biopsy and positive antineutrophil cytoplasmic antibody. The electrocardiogram showed changes suggestive for myocarditis. A transthoracic and trans esophageal echocardiogram revealed left ventricular systolic dysfunction, thickened left atrial and ventricular wall and vegetation on mitral valve. Blood cultures were negative. Myocarditis and nonbacterial thrombotic endocarditis (NBTE) were diagnosed. As far as we know, NBTE is a rare manifestation of GPA and its presentation with myocarditis is not reported to date. This case indicates the uncommon manifestations of GPA and notifies the importance of performing echocardiography in order to prevent life threatening cardiac complications of the disease.